(untitled) (Historia, 2022)
Based on original archival research and oral interviews, this article examines archives creation and the preservation of the history of the multinational mining companies of Selection Trust (ST) and Anglo-American Corporation (AAC) in Zambia’s Copperbelt region between 1922 and 2000. The investment of foreign capital by multinational companies in the Copperbelt mines from the 1920s, marked the genesis and formal preservation of business archives in the Copperbelt. This article argues that although the ST and ACC archives were privately owned and strictly preserved for corporate interests and administrative efficiency, these documents eventually became publicly available because of Zambia’s political independence and the nationalisation of the mining industry in the 1960s. In the early 1970s, the United National Independence Party (UNIP) government nationalised the Zambian mines and merged the two multinational companies to form the Zambia Consolidated Copper Mines (ZCCM). Consequently, in 1982, the ST and ACC archives were merged. However, following the complete privatisation of the mining industry in 2000 the identity of mining archives reverted to private entities. This article provides new and significant insights into the power and role of regional and local political-economic shifts in determining the nature and identity of business archives in Zambia.